Learning skills from distance: a solar photovoltaic site survey from students’ view - Masek, Alias; Muhammad Nurtanto, Muhammad Nurtanto; Nur Kholifah, Nur Kholifah; Mutohhari, Farid; Zainal, Rizal (2022)
This study was to investigate the effectiveness of teaching skills using online medium for solar site survey, as well as students perceived on learning site survey using online medium. A survey study was conducted that involved 30 students who enrolled in a solar PV installation and maintenance course. An online questionnaire consists of eight items using five points Likert Scale were adapted from previous study, gauging students perceived on learning site survey using online medium (i.e. online lecture, WhatsApp, chat, voice, picture, short video clips, and learning management system-LMS). An assignment was used to indicate students’ performance in site survey skills, including a short test to gauge students’ technical skills knowledge, consisting of a total of 10 Multiple Choices Questions (MCQ), were developed by referring to the syllabus, under subtopic of solar site survey. Technical knowledge questions were divided into two types namely, items for testing concept (i.e. tools), principles (i.e. relationship of sunlight and shading) and procedures (i.e. application of knowledge). The result: Student average achievement in technical knowledge test was 68.3% (M = 6.83, SD = 1.64); student average achievement mark in a solar site survey sketch is 62.8%; and students perceived on learning solar PV site survey was at high level (M = 3.99, SD = 0.69). It is concluded that solar PV site survey skills are possible to be implemented from distance through online medium, and it can be improved through a more video packaged in the form of live sessions.